Peran Kaum Muda Kotagede: Konservasi dan Regenerasi Kelangsungan Usaha Kreatif Perak - Elizabeth Widya Nidianita; Dewi Puspitasari (Universitas Gadjah Mada, 2017)
Creative endevour of silver in Jagalan Village started since the 16th century and 17th and reached the heyday in 1910 and 1970-1980. But after Monetary Crisis (1998), Bali Bombing (2002) and Earthquake (2006) the number of silversmiths were declining continously, making artisans reluctant to share their skills possessed to future generations. This condition brought up response and strategies of youth in applying the concept of 3T (talent, technology and tolerance) toward the sustainability of creative business of Kotagede silver handicraft in Jagalan Village. This research uses qualitative research method and descriptive analysis. Research findings in this research is youth as the actor to potential and capacity as agent of change, starting from motivation, the process, space to the implementation of through movement conservation and efforts to regenerate silversmiths mapping and quarrying of tourism village’s, make video tourism promotion and marketing couple ring to Hongkong, then hold workshop design for makers, Jagalan Festival and a healthy walking. Secondly, movement conservation as an effort to regeneration in which implemented through the application of 3T concept collaboratively. Talents is pertaining to family background, social environment and youngster’s education; tolerance is openness in interaction toward various parties and technology facility for marketing and publication. Variety of initiatives and the ideas are implemented into 6 ( six ), education by providing the space for discussion, marketing for traditional foods and of silver craft products , publication in order to provide a chance silversmiths in accessing the market, innovation make craftsman having the bargaining power as artisan (expert), maintenance and movement to be preservation of cultural heritage ancestors. One of the output of these efforts is Jagalan Tlisih Kampung.